East-Central Europe-World’s Coronavirus Death Center - Craven, John S (Archives of Community Medicine and Public Health, 2022)
A review of the Countries with the highest coronavirus death rates in the world was made on February 11, 2022. The world’s average death rate that day was 746. It was not surprising to see the countries with the largest number of deaths having death rates 300- 400% of the world’s average. What was alarming was that the ten countries with the world’s highest death rates had death rates 400-800% of the world’s average and most of them were located in East-Central Europe. This paper focuses on understanding the implications of this.